Active control of low frequency sound absorption of large sized micro-perforated panel absorber by using point source. (1st January 2022) - Ma, Xiyue; Chen, Kean; Wang, Lei; Liu, Yang; Ding, Shaohu
Abstract: This paper presents a theoretical investigation on actively controlling the low frequency sound absorption of large-sized micro-perforated panel absorber (MPPA) by using point source placed in the cavity. The large sized active MPPA is an easily implemented and cost-effective scheme for achieving superior low frequency sound absorption in large area. The modal analysis approach is used to establish the theoretical model of such active MPPA. The physical mechanism of active control is analyzed and some physical insights are summarized. Based on these conclusions, the error sensing strategy of the large sized active MPPA is also constructed. Finally, experimental tests are carried out to validate the theoretical modeling and findings. Results show that the sound absorption performance can be significantly improved after control in a wide low frequency range below the cutoff frequency. The optimal position of the point source is at the central of the cavity section, in which case the cutoff frequency is the largest and depends on the length of the short side of the active MPPA. The control mechanism of sound absorption improvement is to enhance the Helmholtz type resonant absorption by suppressing the cavity sound field. The high order cavity mode (except for (0, 0, 0) mode) has no contribution to sound absorption improvement due to the symmetrical property of their mode shape. The pressure release (PR) and impedance matching (IM) strategies are still applicable for the large sized active MPPA. Relative small sized cavity or low frequency excitation can guarantee the uniformity of the cavity sound field after control, which is conducive to achieve remarkable improvement of sound absorption.